American studies - Menand, Louis; McLarty, Ron (Minneapolis, MN HighBridge Co., 2002)
Presents a collection of essays on American art, American thought, and American life.
The principals of Oliver Wendell Holmes -- Richard Wright, the hammer and the nail -- The last emperor, William S. Paley -- A friend writes, the old New Yorker -- Norman Mailer in his time -- Life in the stone age -- The popist, Pauline Kael -- Lust in action, Jerry Falwell and Larry Flynt -- Laurie Anderson's United States.
Unabridged.
Compact disc.
Read by Ron McLarty.
100015
Keywords: United States -- Intellectual life -- 20th century; United States -- Civilization -- 20th century